Marriage and parenthood (London : Friends' Book Centre)
1934-11 1934 1930s 22 pages 6 Marriage and Parenthood Biologically the engaged relationship is an unnatural one, and long engagements often lead to a sense of strain and may even affect the health of both parties. The emotional difficulties which sometimes arise at this stage are quite likely to be the product of unnatural strain rather than of real incompatibility. Young people do well not to set their ideas of material prosperity too high, but to take the opportunity of making a home together on a very simple scale rather than wait a longer time for a greater degree of comfort or security. The difficulties in the way of early marriage which our present social system involves are real and hard to overcome, but the early struggles shared in a spirit of adventure can do much to unite husband and wife and to lay a sure foundation on which to build up the family life of the future. In some cases marriage can only be made possible if the wife continues to work afterwards. This involves many difficulties, including probably the postponement of parenthood, but it is a problem to be decided by each individual couple acccording [according] to their own scale of values. A way of life which is right for one couple may appear little short of disastrous to another, but for each the task is fundamentally the same — to follow the light as they see it, and to be prepared to work and sacrifice for the attainment of an ideal. Another allied problem which is bound to arise after marriage, and may well be considered beforehand, is the question of what work or other interest outside her home the wife is going to carry on after marriage. Some women who have trained for a profession will look upon the surrender of their career as a sacrifice gladly made in the service of the new home, and will find in the life of that home, at any rate for a time, full use for all their creative faculties. But mental stagnation comes all too easily, and in a few years the wife may, without realising it, have allowed her horizon to become completely bounded by the four walls of her home. She may have given up her hobbies, given up her interest in current events, art, literature, social movements, until the time comes when her brain is no longer alert, her conversation is no longer interesting, and her personality suffers. Here again it is impossible to dogmatise, but the probability is that every woman is the better for a definite interest or piece of work outside her home. She will come back all the fresher to her kitchen and her nursery, she will be a better wife and mother, and much more able to keep mentally abreast of her growing children. To make this possible may entail considerable effort for both husband and wife during the busy years of bringing up a family, but it will be 15X/2/478/6